Perilaku Konsumen di Pasar Monopolistik: Studi Kasus Pada Pasar Tradisional Wamena Kabupaten Jayawijaya - Sari, Purnama; Syarifah (Jurnal Honai, 2025)
This study aims to analyze consumer behavior in monopolistic markets in the 3T (Underdeveloped and Transmigration) region, focusing on the traditional market in Wamena City, Jayawijaya Regency. A qualitative approach was used, through in-depth interviews and participant observation with 30 consumers. The results indicate that three main factors influence consumer purchasing decisions: price, product quality, and social interaction. Price is the dominant factor, with consumers actively comparing prices across vendors to obtain the best value. Product quality also contributes to consumer loyalty, especially when the product is proven to be satisfactory and consistent. Furthermore, the social interactions between consumers and vendors in the warm atmosphere of the traditional market contribute to increased comfort and emotional attachment among consumers. These three factors are interrelated in shaping purchasing decisions, and understanding these dynamics is crucial for both vendors and local governments in designing effective marketing strategies and local economic development in the 3T (Underdeveloped and Transmigration) region.